2014
DOI: 10.1007/s10384-014-0324-6
|View full text |Cite
|
Sign up to set email alerts
|

Meibomian gland loss due to trabeculectomy

Abstract: Blebs that occur after trabeculectomy with MMC may be the cause of meibomian gland loss, particularly when the bleb is avascular. The presence of an avascular bleb warrants extra vigilance for decreased meibomian gland secretions because this decrease can lead to tear dysfunction and ocular surface damage, including bleb-wall damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
0
13
1
1
Order By: Relevance
“…When analyzing eyelids, though we found a reduction of MGI, we did not observe significant changes in MGD. This is in contrast with the study of Sagara and coworkers, who documented MG loss after MMC augmented trabeculectomy 18 . This could be due to the fact that they considered patients with a longer follow-up and evaluated the upper eyelid, where MGs may be more disturbed by the direct contact with the bleb.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…When analyzing eyelids, though we found a reduction of MGI, we did not observe significant changes in MGD. This is in contrast with the study of Sagara and coworkers, who documented MG loss after MMC augmented trabeculectomy 18 . This could be due to the fact that they considered patients with a longer follow-up and evaluated the upper eyelid, where MGs may be more disturbed by the direct contact with the bleb.…”
Section: Discussioncontrasting
confidence: 95%
“…When filtration surgery is completely successful it may potentially produce significant improvements of the OS system through different mechanisms. Consequently, the positive change of the OS status may produce potential benefits for the patient QoL; however, on the other hand, the presence of a filtering bleb may induce different OS alterations and maintain, at least in part, a mitigated form of OSD 1618 . These aspects may probably account for the worse QoL experienced by surgically compared to medically treated glaucomatous patients 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Although such treatment has been found to adversely affect the structure of meibomian glands, it remains unclear to what extent these effects are attributable to the preservative or the active ingredient of the eyedrops. [50][51][52][53] A study of meibomian glands in glaucoma patients after trabeculectomy with mitomycin C revealed that the glands adjacent to the bleb were damaged compared with those distant from the bleb, 52 suggesting that drug-induced meibomian gland injury occurred through the palpebral conjunctiva.…”
Section: Treatment With Antiglaucoma Eyedropsmentioning
confidence: 99%
“…Some ocular conditions have been reported to influence FVA. Goto et al reported that dry eye decreased FVA among patients who had normal conventional visual acuity [ 8 , 9 ]. FVA is significantly reflected in the tear functions and ocular surface status of the eye.…”
Section: Introductionmentioning
confidence: 99%